2018
DOI: 10.1101/414821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple QTL underlie milk phenotypes at the CSF2RB locus

Abstract: Background:Bovine milk provides an important source of nutrition in much of the Western world, forming components of many food products. Over many years, artificial selection has substantially improved milk production by cows. However, the genes underlying milk production quantitative trait loci (QTL) remain relatively poorly characterised. Here, we investigate a previously-reported QTL located at the CSF2RB locus, for several milk production phenotypes, to better understand its underlying genetic and molecula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…Multiple protein-coding mutations could be attributed to loci with QTL in both wavenumber and milk composition traits, highlighting genes that appear to be novel to the present study (TGDS and DNAJB13), and genes previously reported in other studies of milk composition traits: GBA [37,65], MTX1 [66], SLC50A1 [36,67], CSF2RB [66,68,69], NCF4 [66,69], TBC1D22A [70], MROH1 [71] and MTARC1 [36]. A number of other QTL that were in strong LD with a PIV were observed in FT-MIR wavenumbers, but not in the FT-MIR predicted milk composition traits.…”
Section: Multiple Ft-mir Wavenumber Qtl Observedsupporting
confidence: 66%
See 2 more Smart Citations
“…Multiple protein-coding mutations could be attributed to loci with QTL in both wavenumber and milk composition traits, highlighting genes that appear to be novel to the present study (TGDS and DNAJB13), and genes previously reported in other studies of milk composition traits: GBA [37,65], MTX1 [66], SLC50A1 [36,67], CSF2RB [66,68,69], NCF4 [66,69], TBC1D22A [70], MROH1 [71] and MTARC1 [36]. A number of other QTL that were in strong LD with a PIV were observed in FT-MIR wavenumbers, but not in the FT-MIR predicted milk composition traits.…”
Section: Multiple Ft-mir Wavenumber Qtl Observedsupporting
confidence: 66%
“…Other wavenumber QTL where a co-localized eQTL was identified within FT-MIR wavenumbers, but not the predicted milk composition traits, included effects that highlighted a number of genes that appear novel to the present study: CLDN8, CSTB, TAB2, LAPTM4A, CAPN5, PMP22, HID1 and THRB; and a number of genes previously reported as having an effect on bovine milk composition: SLC37A1 [66,86], NCF4 [66,69], SLC34A2 [87], TENT5A [40], RNF217 [67], MPC1 [85], XDH [88,89], PAEP [60], DGAT1 [56], RGL1 [90], LTF [91,92] and MUS81 [93]. These results underscore the gain in power that is available when using individual FT-MIR wavenumber phenotypes, compared to using predicted milk composition phenotypes which are linear functions of FT-MIR absorbance values.…”
Section: Co-localized Eqtl Suggest Widespread Regulatory Impacts On Ft-mir Wavenumbersmentioning
confidence: 58%
See 1 more Smart Citation